'Beyond Milestones': A randomised controlled trial evaluating an innovative digital resource teaching quality observation of normal child development. (23rd December 2013) - Connolly, Anne M; Cunningham, Clare; Sinclair, Adriane J; Rao, Arjun; Lonergan, Amy; Bye, Ann ME
<x xml:space="preserve">Abstract</x> Aims The study aimed to create and evaluate the educational effectiveness of a digital resource instructing paediatric trainees in a systematic approach to critical and quality observation of normal child development. Methods A digital educational resource was developed utilising the skills of an expert developmental paediatrician who was videoed assessing normal early child development at a series of critical stages. Videos illustrated aspects of language, sophistication of play and socialisation, cognition, and motor progress. Expert commentary, teaching text and summaries were used. A randomised controlled trial evaluated the resource. Paediatric trainees were recruited from The Sydney Children's Hospitals Network. Outcome measures were repeated at three time points (pre‐teaching, immediate‐post and 1 month) and included self‐rated attitudes, knowledge of markers of development and observational expertise. Qualitative data on teaching usefulness were obtained through open‐ended questions. Results Fifty‐six paediatric trainees (registrar 79%, women 82%; mean age 31 years) completed the pre‐assessment, 46 the immediate‐post and 45 the 1‐month follow‐up (20% attrition). Compared with the Control group, the Teaching group scored higher over time on markers of development (P = 0.006), observational expertise (P < 0.0001), confidence (P = 0.035) and satisfaction (P < 0.0001). Teaching participants valued the video and expert commentary and reported improvement in confidence and understanding and acquiring a more structured approach. Conclusions The 'Beyond Milestones' free online resource for medical professionals <http://learnpaediatrics.org/beyondmilestones/ password=cunningham> improves knowledge, increases confidence and is useful, providing a structured approach to developmental assessment. The techniques taught can be applied to every paediatric consultation.